2015
DOI: 10.1080/00222895.2014.998331
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mobility in a Divided Attention Task in Older Adults With Cognitive Impairment

Abstract: Motor disorders may occur in mild cognitive impairment (MCI) and at early stages of Alzheimer's disease (AD), particularly under divided attention conditions. We examined functional mobility in 104 older adults (42 with MCI, 26 with mild AD, and 36 cognitively healthy) using the Timed Up and Go test (TUG) under 4 experimental conditions: TUG single task, TUG plus a cognitive task, TUG plus a manual task, and TUG plus a cognitive and a manual task. Statistically significant differences in mean time of execution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…EF is a cognitive capacity composed of other cognitive domains (e.g., shifting, working memory, and inhibition), which allow the subject to create, develop, and perform a strategy to perform an aim, evaluate the outcomes, and, if necessary, change the strategy during or at the end of the task, creating new strategies for the future [40]. Therefore, EF is an essential cognitive domain for maintenance of autonomy and independence during aging, and its impairment is observed in intermediate conditions (e.g., mild cognitive impairment), as well as during several psychopathological conditions, including Alzheimer's disease [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EF is a cognitive capacity composed of other cognitive domains (e.g., shifting, working memory, and inhibition), which allow the subject to create, develop, and perform a strategy to perform an aim, evaluate the outcomes, and, if necessary, change the strategy during or at the end of the task, creating new strategies for the future [40]. Therefore, EF is an essential cognitive domain for maintenance of autonomy and independence during aging, and its impairment is observed in intermediate conditions (e.g., mild cognitive impairment), as well as during several psychopathological conditions, including Alzheimer's disease [15]. …”
Section: Discussionmentioning
confidence: 99%
“…This task was performed out loud, allowing the evaluators to confirm if the volunteers were, in fact, accomplishing the task. The time spent to perform the task was recorded for evaluation [15]. …”
Section: Methodsmentioning
confidence: 99%
“…The results showed that TUG 2 and 4 were more impaired than TUG 1 and 3, which suggests that the cognitive tests interfere with functional mobility more than the motor tests. This finding underlines the impression of the task of cognition as the highest requesting factor in the divided attention task (28). These phases of the TUG test could be used to discriminate between MCI and AD groups, due to the fact that those suffering from AD require more time to complete this task.…”
Section: Discussionmentioning
confidence: 94%
“…Pettersson et al (27), concluded that gait was influenced in a dual-task condition for individuals with AD compared with normal people. De Melo-Borges et al (28), stated that in all phases of a TUG task (Table 1), participants with mild cognitive impairment (MCI) performed worse than the normal group and better than the AD group, especially on the divided attention task.…”
Section: Rodda Et Al (2011) (14)mentioning
confidence: 99%
“…Timing will start when participants get up from the chair and will stop when their back touches the backrest of the chair again [31]. After completing the standard TUG test, participants will be asked to perform TUG combined with a verbal fluency task (i.e., naming as many animals as they can remember), with a motor task (i.e., carrying a full cup of water), and with both cognitive and motor tasks (i.e., performing the verbal fluency test while carrying a full cup of water) [32].…”
Section: Assessment Of Muscle Strength Physical Function and Disabimentioning
confidence: 99%